2019
DOI: 10.1159/000499936
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic Stress Disorder Is a Risk Factor for Multiple Addictions in Police Officers Hospitalized for Alcohol

Abstract: <b><i>Background:</i></b> In police officers, posttraumatic stress disorder (PTSD) is associated with alcohol use disorder (AUD), but we lack data on the association between PTSD and other substance-related and addictive disorders. <b><i>Objectives:</i></b> We assessed whether PTSD could be a risk factor for different substance-related and addictive disorders in police officers, including alcohol, tobacco, cannabis, and gambling. <b><i>Method:</i&g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 47 publications
0
4
0
1
Order By: Relevance
“…The CAST has been widely applied to assess cannabis abuse (Amado et al, 2020;Arias-de la Torre et al, 2020;Blankers et al, 2014;Brunault et al, 2019;Golpe, Gómez, Braña, Varela, & Rial, 2017). It also served as a massive screening tool in national-scale surveys, but not always using the same correction version and the same cut-off points (Beck and Legleye, 2003;EMCDDA, 2020b; Presidenza del Consiglio dei Ministri & Dipartimento per le Politiche Antidroga, 2018; Spanish Observatory on Drugs and Addictions, & Government Delegation for the Spanish National Drugs Plan, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The CAST has been widely applied to assess cannabis abuse (Amado et al, 2020;Arias-de la Torre et al, 2020;Blankers et al, 2014;Brunault et al, 2019;Golpe, Gómez, Braña, Varela, & Rial, 2017). It also served as a massive screening tool in national-scale surveys, but not always using the same correction version and the same cut-off points (Beck and Legleye, 2003;EMCDDA, 2020b; Presidenza del Consiglio dei Ministri & Dipartimento per le Politiche Antidroga, 2018; Spanish Observatory on Drugs and Addictions, & Government Delegation for the Spanish National Drugs Plan, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 182 alcohol-dependent patients without ADHD, who were administered the same trauma questionnaire as in our study, 55% reported trauma exposure [26]. Since both ADHD and SUDs are associated with increased rates of PTEs over the lifespan [14,[27][28][29][30], it seems likely that the co-occurrence of both disorders leads to an even higher rate.…”
Section: Discussionmentioning
confidence: 71%
“…This is consistent with previous research in police and who report low levels of understanding about where to get help (Hofer & Savell, 2021; Richards et al, 2021). Without adequate awareness of treatment options, police members are unlikely to access treatment and may adopt maladaptive coping strategies (e.g., substance use; Brunault et al, 2019). To improve awareness, the findings suggest avoiding an overreliance on internal emailing systems to promote supports available (which police members often ignore) and consider combinations of digital (e.g., email), physical (e.g., flyers), and in-person communications (e.g., workshops/seminars with respected presenters) to increase awareness.…”
Section: Discussionmentioning
confidence: 99%